2018
DOI: 10.1177/1455072518772397
|View full text |Cite
|
Sign up to set email alerts
|

What makes people with gambling disorder undergo treatment? Patient and professional perspectives

Abstract: Aims: The aim of the article is to identify factors which bring people with gambling disorder to undergo treatment. We are interested in exploring motives that trigger change; identifying factors determining choice of facility; recognising barriers and facilitators appearing during treatment. Design: Semi-structured interviews were conducted in Poland with people with gambling disorder, as well as with social workers, therapists, General Practitioners (GP) and psychiatrists. Purposive sampling was applied in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Integration of services is especially important for those who lack financial security in order to minimize the need to travel to multiple service providers to meet the co-morbid health and social issues faced by people who are experiencing poverty and homelessness. As with previous research, we identified that long wait lists are deterrents to care (Wieczorek & Dąbrowska, 2018). From previous research, we know that recovery from problem gambling is enhanced when patients feel their own sense of empowerment (Pickering et al, 2019).…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Integration of services is especially important for those who lack financial security in order to minimize the need to travel to multiple service providers to meet the co-morbid health and social issues faced by people who are experiencing poverty and homelessness. As with previous research, we identified that long wait lists are deterrents to care (Wieczorek & Dąbrowska, 2018). From previous research, we know that recovery from problem gambling is enhanced when patients feel their own sense of empowerment (Pickering et al, 2019).…”
Section: Discussionsupporting
confidence: 61%
“…Notably, integration and coordination of services is integral to ensure that people have easy access to services. Staff training will ensure an appropriate level of awareness of problem gambling in populations who are experiencing disadvantage, the integration of tools into practice, training on screening for problem gambling, cultural influences on problem gambling and treatment seeking, and recognition and training on the importance of a gender/sex-responsive approach to care (Lewis et al, 2016;Priebe et al, 2012;Wieczorek & Dąbrowska, 2018). Integration of services is especially important for those who lack financial security in order to minimize the need to travel to multiple service providers to meet the co-morbid health and social issues faced by people who are experiencing poverty and homelessness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This might mean a worse perception of professionals towards gambling and problem gambling compared to in nations where the structure of the gambling industry is different. We believe further research using the GGPPQ in various regions with consideration for such characteristics will provide regionally comparable data which will shed light on professionals’ attitudes towards gambling and problem gamblers, how they are formed and how they can be improved ( Wieczorek & Dąbrowska, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…improved through years of experience, but that providing training programmes as well as ongoing support during practice is important (el-Guebaly et al, 2000;Livingston et al, 2012;Manning et al, 2020;Rodda et al, 2018;Silins et al, 2007;van Boekel et al, 2013;Wieczorek & Dąbrowska, 2018). In Japan, complaints have been made by the government that many healthcare professionals enter clinical practice without sufficient training on problem gambling (Ministry of Health Labour and Welfare, 2021).…”
Section: Scale Validitymentioning
confidence: 99%